Genetic evaluation of short-term selection in synthetic coloured broiler male and female lines— Direct and correlated responses - REDDY, B L N; CHATTERJEE, R N; RAJKUMAR, U; NIRANJAN, M; RAJARAVINDRA, K S; BHATTACHARYA, T K (The Indian Journal of Animal Sciences, 2013)
Broiler male line (PB-1) and female line (PB-2) were under continuous mass selection for 6 week body weight andindependent culling level was applied for 40 week egg production in female line. Data obtained over 5 generations on juvenile body weights and production traits was analyzed to evaluate the short-term direct and correlated responses inboth lines. In male line, genetic responses for 6 WK body weight, 20 WK body weight,40WK body weight, age atsexual maturity,32 WK egg weight,40 WK egg weight and 40 WK egg production were 31.6±21.31 g, –80.10±111.98 g,–38.60±102.58 g, 0.50±2.31days, 0.24±2.40 g,-0.49±0.81 g and 1.80±4.69eggs respectively. On genetic scale 6 WKbody weight was improved significantly (P